CYP17A1–ATP2B1 SNPs and Gene–Gene and Gene–Environment Interactions on Essential Hypertension - Wei, Bi-Liu; Yin, Rui-Xing; Liu, Chun-Xiao; Deng, Guo-Xiong; Guan, Yao-Zong; Zheng, Peng-Fei (Frontiers in Cardiovascular Medicine, 2021)
Background: The association between the CYP17A1 and ATP2B1 SNPs and essential hypertension (Referred to as hypertension) is far from being consistent. In addition to the heterogeneity of hypertension resulting in inconsistent results, gene-gene and gene-environment interactions may play a major role in the pathogenesis of hypertension rather than a single gene or environmental factor. Methods: A case-control study consisting of 1652 individuals (hypertension, 816; and control, 836) was conducted in Maonan ethnic minority of China. Genotyping of the four SNPs was performed by the next generation sequencing technology. Results: The frequencies of minor alleles and genotypes of 4 SNPs were different between the two groups (P < 0.01). According to genetic dominance model analysis, three (rs1004467, rs11191548 and rs17249754) SNPs and two haplotypes (CYP17A1 rs1004467G-rs11191548C and ATP2B1 rs1401982G-rs17249754A) were negatively correlated, whereas rs1401982 SNP and the other two haplotypes (CYP17A1 rs1004467A-rs11191548T and ATP2B1 rs1401982A-rs17249754G) were positively associated with hypertension risk (P < 0.05 for all). Two best significant two-locus models were screened out by GMDR software involving SNP-environment (rs11191548 and BMI ≥ 24 kg/m2), haplotype-environment (CYP17A1 rs1004467G-rs11191548C and BMI ≥ 24 kg/m2) interactions (P < 0.05). The subjects carrying some genotypes increased the hypertension risk. Conclusions: Our outcomes implied that the rs1004467, rs11191548 and rs17249754 SNPs and CYP17A1 rs1004467G-rs11191548C and ATP2B1 rs1401982G-rs17249754A haplotypes have protective effects, whereas the rs1401982 SNP and CYP17A1 rs1004467A-rs11191548T and ATP2B1 rs1401982A-rs17249754G haplotypes showed adverse effect on the prevalence of hypertension. Several SNP-environment interactions were also detected.